(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The consequences of the global warming of the world’s climate are felt in the rainfed regions of the republic. Climate change will have a negative impact on the food security of the population living in dry regions. As a result of global warming, the frequency of droughts has accelerated, until 2010, severe droughts occurred every 8-10 years. In recent years, it has been observed that during the period of grain filling and ripening of grain crops, drought occurs along with strong anomalous heat.